Conflicts of Interest in Self-Regulation : Can Demutualized Exchanges Successfully Manage Them? - Carson, John W. (World Bank, Washington, DC, 2014)
The author examines the implications of demutualization of financial exchanges for their roles as self-regulatory organizations. Many regulators and exchanges believe that conflicts of interest increase when exchanges convert to for-profit businesses. Demutualization also changes the nature of an exchange's regulatory role as broker-dealers' ownership interests are reduced. These factors are leading to reduced regulatory roles for exchanges in many jurisdictions. The resulting changes have significant implications for regulation of financial markets, especially as exchanges are the only self-regulating organizations (SROs) in most countries. Major changes in the role of exchanges require a rethinking of the allocation of regulatory functions and the role of self-regulation, as well as stronger mechanisms to mitigate conflicts of interest. Carson looks at the views of both exchanges and regulators on these issues in Asian, European, and North American jurisdictions where major exchanges have converted to for-profit businesses. He finds that views on the conflicts of interest faced by demutualized exchanges vary widely. In addition, the tools and processes used by exchanges and regulators to manage conflicts also differ significantly across jurisdictions. The author concludes that new and greater conflicts result from demutualization and canvasses the regulatory responses in the jurisdictions examined.